Attributes that influence turnover in public institutions: evidence from a bibliometric analysis - Gonçalves, Wellington; Romeiro, Pamella de Medeiros (Brazilian Journal of Production Engineering, 2025)
Turnover in the public sector represents a growing challenge for human resource management, as it directly affects organizational efficiency, service quality, and institutional costs. This study mapped and categorized the predictive factors of turnover in public institutions and thus contributes both to academic research and managerial practice. A systematic review with bibliometric analysis and meta-analysis was conducted, using data from the Web of Science database covering the period 1978–2025. The application of multiple correspondence analysis and cluster analyses allowed the identification of five interrelated dimensions influencing public sector turnover: working conditions and well-being, organizational policies and culture, leadership and interpersonal relations, intrinsic motivation and organizational citizenship, and structural factors. The findings reveal that the decision to remain in or leave an organization does not stem from a single aspect but from the interplay of individual, relational, and institutional variables. Based on these insights, public managers should prioritize policies aimed at improving quality of work life, adopting fair leadership styles, and implementing professional recognition practices to mitigate turnover. This study contributes to the field by proposing an original analytical framework that could guide future investigations and support the development of more effective human resource management strategies in the public sector.
Keywords: turnover; Serviço Público; Gestão de Pessoas; Rotatividade, Servidores, Administração pública; Gestão estratégica de pessoas